Understanding agrobiodiversity and nutritional outcomes: a study of socio-economic differentiation among smallholder vegetable farming in northern Vietnam - Hoang, K.; Nabuuma, D.; Swaans, K.; Naziri, D.; Vernooy, R. (Informa UK Limited, 2025)
In recent years, smallholder farmers in northern Vietnam improved their vegetable cultivation with positive results for agrobiodiversity and nutrition. An unresolved question was if socio-economic differences among smallholder farmers influenced these outcomes, which this article addresses through a combined descriptive, bivariate, and multivariate analysis of household survey data. The study provides critical insights into the relationship between agrobiodiversity and dietary diversity among three ethnic groups in the uplands of northern Vietnam. Concerning crop diversity, the Hmong group cultivated the lowest number of crops (14) and the Thai group the highest (19), with Dao in-between (17). Total area of land cultivated and the area of vegetable production impacted positively on farm-level agrobiodiversity. Findings indicate that the vegetable production area is the main driver of vegetable species richness, with farmers allocating larger areas to these crops having considerably more diversity than farmers with smaller vegetable areas. Larger vegetable production areas, higher Fruit Species Richness, lower Staple Species Richness, larger household, and higher education contributed to a more diverse diet. The findings call for a more careful analysis of how differences in assets, ethnicity, and household characteristics influence livelihood improvement outcomes. These differences need to be better accounted for in policy interventions.